IMPLEMENTASI DIGITAL MARKETING BERBASIS AI SEBAGAI UPAYA PENINGKATAN KOMPETENSI SISWA SMK YASINDO PARUNG - Fauziah, Eva; Faizura Zadri; Philip Sun Bunaryo (Universitas Pamulang, 2025)
This community service activity aims to improve participants' knowledge and skills in implementing Artificial Intelligence (AI)-based digital marketing as an effective promotional strategy in the digital era. This training covers basic digital marketing concepts, an introduction to AI technology, and the application of various AI tools such as ChatGPT, Canva AI, Google Analytics, and ManyChat in content creation, data analysis, and customer service automation. Through interactive outreach methods, case studies of well-known brands such as Domino's Pizza, Shopee, and Spotify, and hands-on training, participants learned how AI improves the efficiency, personalization, and accuracy of digital marketing strategies. The training results demonstrated improved participant skills in creating creative content, automatically managing social media, and analyzing data-driven consumer behavior. Therefore, utilizing AI in digital marketing is a strategic step to strengthen competitiveness, promotional efficiency, and sustainable innovation among businesses and creative individuals.